2010
DOI: 10.1007/s00726-010-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential amino acids or glutamine deprivation on intestinal permeability and protein synthesis in HCT-8 cells: involvement of GCN2 and mTOR pathways

Abstract: GCN2 and mTOR pathways are involved in the regulation of protein metabolism in response to amino acid availability in different tissues. However, regulation at intestinal level is poorly documented. The aim of the study was to evaluate the effects of a deprivation of essential amino acids (EAA) or glutamine (Gln) on these pathways in intestinal epithelial cells. Intestinal epithelial cell, HCT-8, were incubated during 6 h with 1/DMEM culture medium containing EAA, non EAA and Gln, 2/with saline as positive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…To better understand the underlying mechanisms involved in the effects of protein delivery, we studied intracellular phosphokinases as previously described (19,34). We did not observe the activation of the mTOR pathway that usually mediates the effects of amino acids on protein translation in muscle (35) and intestinal cells (12,16,20,36). Neither mTOR nor downstream components such as the p70S6kinase or factor 4E binding protein 1 were affected by the protein supply.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…To better understand the underlying mechanisms involved in the effects of protein delivery, we studied intracellular phosphokinases as previously described (19,34). We did not observe the activation of the mTOR pathway that usually mediates the effects of amino acids on protein translation in muscle (35) and intestinal cells (12,16,20,36). Neither mTOR nor downstream components such as the p70S6kinase or factor 4E binding protein 1 were affected by the protein supply.…”
Section: Discussionmentioning
confidence: 92%
“…Glutamine, which is the preferential substrate of rapidly dividing cells (ie, enterocytes and immune cells), is associated with less-infectious complications in critically ill patients (10) that could be partly due to the maintenance of gut barrier function (11). In vitro data showed that glutamine increased protein synthesis in intestinal epithelial cells (12)(13)(14)(15)(16). In animals, glutamine enhanced intestinal protein synthesis in hypercatabolic dogs (17) but not in malnourished rats (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic glutamine synthetase, which is a longevityrelated gene, is responsible for this synthesis Small intestine and kidneys are the major sites of glutamine utilization under normal or acidotic conditions Intracellular glutamine concentration generally decreases in catabolic states. In humans, this change can be prevented or attenuated by glutamine supplementation (enteral or parenteral) The liver can synthesize or degrade glutamine, depending on the nutritional conditions (2)Regulatory roles of glutamine in cell-specific processes Boukhettala et al (2012), 25 Brasse-Lagnel et al (2009), 26 Yi et al (2015) 27 , BrasseLagnel (2010), 28 Curi et al (2005) 29 (2007), 30 Deniel et al (2007), 31 Larson 34 Matés et al (2006), 37 Nakajo et al (2005), 38 Naomoto et al (2005), 39 Nishikawa et al (2007), 40 Papaconstantinou (2000), 41 Rhoads & Wu (2009), 42 Roth et al (2002), 45 Roth (2007), 43 (2008), 44 Rutten et al Abbreviations: ATP, adenosine triphosphate; EAAs, essential amino acids; NEAAs, nonessential amino acids; NF-jB, nuclear factor jB.…”
Section: Glutamine Signaling In the Livermentioning
confidence: 99%
“…12,13 The dialysis bag allowed the transfer of the released drug molecules into the release media while intercepting the nanoparticles. The dialysis bag (molecular weight range: 8,000 to 14,000; Sigma-Aldrich) was boiled for more than 30 minutes and soaked in the release media overnight prior to the experiment; the release media was double-distilled water.…”
Section: Characterization Of Hsya-loaded Nanoparticles Droplet Size Amentioning
confidence: 99%